2009
DOI: 10.2967/jnumed.108.055533
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Targeting of 99mTc-Labeled Recombinant Human β-Defensin-3 in an Animal Model of Infection: A Feasibility Pilot Study

Abstract: Human b-defensin-3 (HBD-3) is an antimicrobial peptide with bactericidal effects on many gram-positive and gram-negative bacteria and some yeast species and, if radiolabeled, might be used to distinguish bacterial infection from sterile inflammation. The goals of the present study were to develop methods for radiolabeling HBD-3 with 99m Tc and to perform preliminary investigations on 99m Tc-labeled HBD-3 as a means to evaluate induced infection in an animal model. To this purpose, Staphylococcus aureus-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Accurate and early detection of infectious and non-infectious is of great importance for elucidation of the cause of the disease, early prevention of the onset of complications, and rapid implementation of a tailored therapeutic regimen [55], [56]. In the study, the significant difference of the expression of HBD-3 which has been connected with antibacterial tasks has also been found between inflamed interfacial membranes and not inflamed interfacial membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate and early detection of infectious and non-infectious is of great importance for elucidation of the cause of the disease, early prevention of the onset of complications, and rapid implementation of a tailored therapeutic regimen [55], [56]. In the study, the significant difference of the expression of HBD-3 which has been connected with antibacterial tasks has also been found between inflamed interfacial membranes and not inflamed interfacial membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, a feasible application of HBD-3 may even help doctors make a distinction between periprosthetic joint infection and aseptic loosening by intraoperative histological biopsy of the interfacial membranes. Another more practical approach, in further clinical studies, maybe to radiolabel HBD-3 with the goal of assessing the potential of HBD-3 radiolabeled as a radiopharmaceutical for imaging periprosthetic joint infection because the anti- microbial peptide HBD-3 selectively bind to the bacterial cell membrane [55], [56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 68 Ga‐NOTA‐UBI fragments were also reported to show bacterial selectivity and specificity in vitro . Furthermore, human neutrophil peptide, neutrophil elastase inhibitor peptide human β‐defensin, and human lactoferrin‐derived peptide have also been successfully evaluated for imaging bacterial infection …”
Section: Introductionmentioning
confidence: 99%
“…These investigators speculated that decreased sensitivity over time may have been related to the effects of the protective biofilm or glycocalix secreted by the bacteria. Would the results of Liberatore et al (24) have been different had they injected greater or lesser quantities of bacteria into the animals or had they increased or decreased the interval between inoculation and tracer injection?…”
mentioning
confidence: 99%
“…In this issue of The Journal of Nuclear Medicine, Liberatore et al (24) report on microbial targeting with a 99m Tc-labeled antimicrobial peptide, recombinant human b-defensin-3, that exerts bactericidal effects on grampositive and gram-negative bacteria, as well as on some yeasts. The investigators demonstrated that by 3 h after injection, tracer uptake in a Staphylococcus aureus infection model was significantly higher than uptake in sterile inflammation, lending credence to the concept of a ''specific'' infection imaging agent.…”
mentioning
confidence: 99%